Utilization of palm oil fuel ash as silica source of Ni/SBA-15 for carbon dioxide reforming of methane - Setiabudi, Herma Dina; Aishah, Abdul Jalil; Chin, Sim Yee; Nurul Aini, Mohamed Razali (2018)
Climate change has become one of the main concerns of humanity in recent century. As carbon dioxide (CO2) and methane (CH4) are considered as the main contributor to greenhouse gases (GHGs), the transformation of these two gases into more valuable products (syngas) by CO2 reforming of CH4 (CRM) has been attracted extensive attention. CRM has been studied extensively using variety of supported metal catalysts including Ni/SBA-15. However, the cost for the large-scale manufacture of SBA-15 is high, owing to the cost of both templates and silica sources. Therefore, the objective is to synthesis the Ni/SBA-15 using palm oil fuel ash (POFA) as a silica source for CRM. The preparation of POFA sodium silicate (POFA-Na2SiO3) was done using sodium hydroxide (NaOH) fusion method under several parameters including NaOH/POFA mass ratio, fusion temperature and H2O/NaOH-fused POFA mass ratio. The optimum condition was achieved at NaOH/POFA mass ratio of 2:1, fusion temperature of 550oC and H2O/NaOH-fused POFA mass ratio of 4:1, with maximum silica content of 40570 ppm. The obtained POFA-Na2SiO3 was used as the silica source for the synthesis of Ni/SBA-15(POFA) by studying the effect of Na2SiO3-POFA/P123 mass ratios (2.0, 2.9 and 4.0) and Ni loadings (1-5 wt%). The effect of Na2SiO3-POFA/P123 ratios revealed that the optimal synthesis ratio was at 2.9, which produces a well-defined hexagonal framework, smaller NiO particles, stronger Ni-support interaction, homogeneous metal distribution and higher amount of basic sites. The effect of Ni loadings revealed that the highest catalytic performance and stability was marked by 3wt% owing to the well dispersion Ni particles on the SBA-15 surfaces that creates a good metal-support interaction (Ni–O–Si) and considerable amount of basic sites, which then enhances its catalytic performance. This study affirmed that POFA can be served as silica substitution of Ni/SBA-15. Optimal Ni/SBA-15 was found at Na2SiO3-POFA/P123 ratio of 2.9 and Ni loading of 3wt%, with CH4 conversion = 87.11%, CO2 conversion = 76.51%, H2/CO = 0.84.